Neuroanatomical Substrates of Rodent Social Behavior: The Medial Prefrontal Cortex and Its Projection Patterns - Ko, Jaewon (Frontiers in Neural Circuits, 2017)
Social behavior encompasses a number of distinctive and complex constructs that form the core elements of human imitative culture, mainly represented as either affiliative or antagonistic interactions with conspecifics. Traditionally considered in the realm of psychology, social behavior research has benefited from recent advancements in neuroscience that have accelerated identification of the neural systems, circuits, causative genes, and molecular mechanisms that underlie distinct social cognitive traits. In this review, I summarize recent findings regarding the neuroanatomical substrates of key social behaviors, focusing on results from experiments conducted in rodent models. In particular, I will review the role of the medial prefrontal cortex and downstream subcortical structures in controlling social behavior, and discuss pertinent future research perspectives.